Students` learning autonomy: a systematic literature review - Lopes, Rui Pedro (2020)
Higher education finds a set of challenges covering several areas and sectors, resulting from the increasing number of students, their academic and cultural diversity, the demands of the labor market, among others. This massification of training, coupled with budgetary and infrastructural constraints, the uncertainty in the renewal of teaching and non-teaching staff within the requirements to maintain quality and high levels of success, requires creative pedagogical methodologies, especially in the first year, where students face the highest dropout and unsuccess ratio. In this context, Higher Education Institutions encourages teachers to reflect on these issues, providing pedagogical training opportunities and encouragement to implement alternative pedagogical practices, in order to diversify the methodologies so that they can be better adapted to different students’ profile. However, there is still no concern to help the student to organize their autonomous study time. Students have considerable difficulties organizing their personal study time. The fragmentation of the schedule, the distribution of theoretical classes, articulation with the practical learning experiences and the lack of planning of the non-classroom time aggravate the difficulties in time organization. A good organization and planning are fundamental for fostering students’ persistence, motivation and, consequently, provide the possibility for higher success ratios. This study seeks to survey the challenges faced by students and teachers in organizing autonomous study time. Based on a systematic literature review, the definition of concepts, impact of time organization in the students’ success, and the institutional concern with the autonomous learning time (non-presential hours) are researched. It is observed that the difficulty is considerable, although few initiatives are taken to help the students to achieve better organization and a better autonomous learning process.